2021
DOI: 10.1038/s41467-021-23441-0
|View full text |Cite
|
Sign up to set email alerts
|

Retention time prediction using neural networks increases identifications in crosslinking mass spectrometry

Abstract: Crosslinking mass spectrometry has developed into a robust technique that is increasingly used to investigate the interactomes of organelles and cells. However, the incomplete and noisy information in the mass spectra of crosslinked peptides limits the numbers of protein–protein interactions that can be confidently identified. Here, we leverage chromatographic retention time information to aid the identification of crosslinked peptides from mass spectra. Our Siamese machine learning model xiRT achieves highly … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 61 publications
1
24
0
Order By: Relevance
“…For self-CSMs, only 29% more CSMs were identified with DSSO than with BS3 (Figure S10), indicating that self-CSMs are approaching exhaustive coverage at the given experimental detection limit. Similar results were seen when including retention time data of heteromeric and self-CSMs …”
Section: Results and Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…For self-CSMs, only 29% more CSMs were identified with DSSO than with BS3 (Figure S10), indicating that self-CSMs are approaching exhaustive coverage at the given experimental detection limit. Similar results were seen when including retention time data of heteromeric and self-CSMs …”
Section: Results and Discussionsupporting
confidence: 81%
“…Similar results were seen when including retention time data of heteromeric and self-CSMs. 22 To investigate the effect of the cleaved crosslinker fragments on the overall crosslink search performance, we performed another search in which the DSSO crosslinker was treated as noncleavable. In this search, only 1866 heteromeric CSMs were identified (−74%).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we further found that the retention time can act as an extra dimension to dramatically reduce the false positive hits. Retention time has reported to be a useful feature in the application of MS-based proteomics. We just noticed that a recent paper also used retention time prediction to increase identification of cross-linked peptides . Herein, we found that the monolinked peptides carried out the information on the retention time of the corresponding cross-linked pairs, and the retention time of cross-linked peptides can be well predicted by the use of the retention time of the monolinked peptides.…”
Section: Introductionmentioning
confidence: 85%
“…Larger datasets that include both crosslinking efficiency and crosslinking site(s) of antibody variants bearing crosslinkable groups are needed to enable data-driven approaches to covalent antibody engineering. [77][78][79][80][81][82] Future endeavors using the high throughput yeast-display screening tools reported here can be complemented by mechanistic investigations of successful crosslinkable antibodies using mass spectrometry 37,38,62,65,[83][84][85][86][87][88] and structural 61 characterizations. Ongoing work in our laboratories seeks to identify the residues on LC/A that are directly involved in crosslinking using mass spectrometry (these technically demanding experiments require further methodological development and refinement to enable their application in the sdAb-LC/A system).…”
Section: Discussionmentioning
confidence: 99%